Lethal - Brown, Sandra, 1948- (New York : Grand Central Pub., 2011)
After Honor Gillette is visited by Lee Coburn, a suspected murderer seeking a valuable object that Honor's late husband left behind, they find themselves running from the FBI and untangling a web of corruption and depravity.
Keywords: Hostages -- Fiction; Fugitives from justice -- Fiction